Microfinance In Nepal: Determinants of Viability, Sustainability and Outreach among Grameen, NGO, and Cooperative Microfinance Institutions - Hans Dieter Seibel; Harihar Dev Pant; Dipak Dhungel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1998)
Nepal is one of the poorest countries in the world, with 70% of its population below the poverty line. Subsidized national poverty lending programs have failed to attain viability, mobilize savings and reach the poor in significant numbers. Informal institutions such as the ubiquitous dhikuti were ignored. During the 90s the government has created a new policy environment focusing on decentralization, poverty alleviation, economic and financial liberalization, and a differentiated legal framework for microfinance institutions (MFIs). This has paved the way for innovations such as the establishment of Grameen replicators as banks; the upgrading of dhikuti activities to savings and finance companies with doorstep services; and the transformation of the small farmer credit operations of the Agricultural Development Bank into profitable local MFIs cooperatively owned by their members. In the framework of a wider UNDP-supported program of the Asian and Pacific Development Centre in Kuala Lumpur on Microfinance for the Poor in Asia-Pacific, six MFIs were selected from Nepal and analyzed in terms of outreach to the poor, resource mobilization, viability and sustainability: two Grameen Bank replicators - one a bank and one an NGO; two NGOs sponsored under the government's Rural Self-Reliance Fund; and two cooperatives. The outreach of the NGOs was found to be insignificant while the outreach of the Grameen Bikas Bank at the regional level and of the cooperatives at the local level was sizeable. The cooperatives performed well in terms of portfolio efficiency and were found to be financially viable; the NGOs did reasonably well; while the Grameen Bikas Bank, substituting donor funds for internal resources, was lowest (though improving) in operational and financial self-sufficiency - despite a 100% on-time repayment rate. On the whole all MFIs appeared rather hesitant to utilize their newly won freedom to vigorously expand their market, mobilize internal resources, and differentiate their products and interest rates.
Keywords: 330; Informeller Finanzsektor; Klein- und Mittelunternehmen; Finanzierung; Bewertung; Nepal